Oryzias latipes (JAPANESE MEDAKA) as genetic model to study causative genes of epilepsy disease: an in-silico approach - Umi Nabila Mat Yusuf,; Lyena Watty Zuraine Ahmad,; Roziah Kambol,; Farizan Aris,; Nurul Aili Zakaria,; Norfatimah Mohamed Yunus, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Epilepsy is a chronic neurological disorder that has affected around 50-70 million people worldwide. Various animal models have previously been used in epilepsy research. To expand the knowledge of the disease, a new animal model is suggested to be explored considering the genetic and phenotypic heterogeneity that contributes to the complexity of the disease. This study was undertaken to analyze 14 causative genes of epilepsy disease in Japanese medaka (Oryzias latipes), humans, and the established model of this disease which is zebrafish (Danio rerio) by assessing the variation in the genes by using MEGA X and predicting the functional motif and secondary structure of the proteins by using PROSITE and GORIV respectively. Results from the variation analysis showed the lowest percentage of conserved genes in Japanese medaka was 60%.50% of the genes of Japanese medaka were found to be more conserved than zebrafish in comparison to a human. The functional motifs present in all genes in Japanese medaka showed the same motifs present in humans. All the secondary structures of Japanese medaka genes were predicted to contain the alpha helix, extended strand, and random coil. In conclusion, it can be inferred that Japanese medaka could be a reliable animal model for epilepsy disease.